2016
DOI: 10.1039/c5fo01299f
|View full text |Cite
|
Sign up to set email alerts
|

Fermented goat milk consumption improves melatonin levels and influences positively the antioxidant status during nutritional ferropenic anemia recovery

Abstract: The aim of the current study was to assess the influence of fermented goat or cow milk on melatonin levels and antioxidant status and during anemia recovery. Eighty male Wistar rats were placed on a pre-experimental period of 40 days and randomly divided into two groups, a control group receiving normal-Fe diet (45 mg kg(-1)) and the Fe-deficient group receiving low-Fe diet (5 mg kg(-1)). Then, the rats were fed with fermented goat or cow milk-based diets with a normal-Fe content or Fe-overload (450 mg kg(-1))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Germinal cells DNA damage decreased in animals fed fermented goat milk. As previously reported 29 , fermented goat milk consumption increases plasma melatonin levels, fact that could explain the increase in TAS recorded in the current study, however there are other nutritional characteristics of goat milk that contributes to the action of melatonin in ameliorating oxidative stress due to modulation of antioxidant defenses. In addition, habitual goat milk consumption has positive effects on enzymatic antioxidant defence (catalase, superoxide dismutase and glutathione peroxidase), limiting the generation of free radicals 15 .…”
Section: Discussionsupporting
confidence: 72%
“…Germinal cells DNA damage decreased in animals fed fermented goat milk. As previously reported 29 , fermented goat milk consumption increases plasma melatonin levels, fact that could explain the increase in TAS recorded in the current study, however there are other nutritional characteristics of goat milk that contributes to the action of melatonin in ameliorating oxidative stress due to modulation of antioxidant defenses. In addition, habitual goat milk consumption has positive effects on enzymatic antioxidant defence (catalase, superoxide dismutase and glutathione peroxidase), limiting the generation of free radicals 15 .…”
Section: Discussionsupporting
confidence: 72%
“…It has also been previously reported that fermented goat milk consumption increased plasma levels of melatonin . This tryptophan derivative is a potent, endogenously produced and diet‐derived free radical scavenger and broad‐spectrum antioxidant, and its protective role in reducing oxidative stress and lipid peroxidation has been reported in various experimental models .…”
Section: Discussionmentioning
confidence: 77%
“…61 The results in Table 3 indicate that anemic rats (G2) had the lowest count of RBCs. Similarly, Moreno-Fernandez et al 62 reported that the induction of anemia in rats was correlated with a signicant decrease in the RBC count. Feeding yogurt-containing inulin led to a signicant increase in the count of RBC.…”
Section: Hematological Parametersmentioning
confidence: 83%